2015
DOI: 10.7220/aesr.2335.8742.2015.9.1.7
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Debt Ratios on Corporate Financial Performance: the Case of Baltic Listed Companies

Abstract: The study reviews the different debt ratios used in empirical research papers; assesses the financial ratios of the Baltic listed companies; and empirically tests the regression between profitability and capital structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Some studies revealed that the debt-to-assets ratio had a positive effect on companies' financial performance (Gill and Obradovich, 2012;Davydov, 2016;Detthamrong et al 2017). However, other studies found a negative association between the debt-to-assets ratio and the firms' performance (Luper and Isaac, 2012;Zelgalve and Berzkalne, 2015;Le et al 2017). Likewise, Amraoui et al 2018found a significant negative relationship between debt-to-assets ratio and financial performance of 52 firms listed in Morocco from 2009…”
Section: Debt-to-income Ratiomentioning
confidence: 99%
“…Some studies revealed that the debt-to-assets ratio had a positive effect on companies' financial performance (Gill and Obradovich, 2012;Davydov, 2016;Detthamrong et al 2017). However, other studies found a negative association between the debt-to-assets ratio and the firms' performance (Luper and Isaac, 2012;Zelgalve and Berzkalne, 2015;Le et al 2017). Likewise, Amraoui et al 2018found a significant negative relationship between debt-to-assets ratio and financial performance of 52 firms listed in Morocco from 2009…”
Section: Debt-to-income Ratiomentioning
confidence: 99%
“…Further, Yildirim (2015) noted that it is better to focus on the change in leverage than leverage itself as an indicator of a firm's growth. In contrast, Zelgalve and Berzkalne (2015) argued that the size of the firm and the type of debt have a bearing on a firm's growth. Their study indicated that larger firms have a less-negative relationship between profitability and debt.…”
Section: Relevant Literaturementioning
confidence: 99%
“…In this section, we first employed a modified static model following previous empirical studies using three alternative measures of financial performance (Siyanbola et al 2015;Zelgalve and Berzkalne 2015;Muriithi et al 2016;Admassu 2016;Abdellahi et al 2017; among others) and taking into account the issue of non-stationary variables:…”
Section: Model Specificationmentioning
confidence: 99%